2018
DOI: 10.18632/oncotarget.25646
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating genomic, transcriptomic and microbiomic alterations lead to canine extreme intestinal polyposis

Abstract: Extreme intestinal polyposis in pet dogs has not yet been reported in literature. We identified a dog patient who developed numerous intestinal polyps, with the severity resembling human classic familial adenomatous polyposis (FAP), except the jejunum-ileum junction being the most polyp-dense. We investigated this dog, in comparison with 22 other dogs with spontaneous intestinal tumors but no severe polyposis, and with numerous published human cancers. We found, not APC mutation, but three other alteration pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 55 publications
(95 reference statements)
2
30
0
Order By: Relevance
“…Strain or substrain level variations may also be biologically relevant; for example, a previous study demonstrated that a specific strain of bacteria, Bifidobacterium animalis AHC7, prevents pathogens from colonizing the canine gut [18]. In addition to the differences in bacterial abundance, differences in functional categories can also be important indicators of gut health [8,12,63,69,73]. However, 16S is not useful in resolving taxonomic differences beyond genus level and it has limited utility in assessing functional profiles of the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strain or substrain level variations may also be biologically relevant; for example, a previous study demonstrated that a specific strain of bacteria, Bifidobacterium animalis AHC7, prevents pathogens from colonizing the canine gut [18]. In addition to the differences in bacterial abundance, differences in functional categories can also be important indicators of gut health [8,12,63,69,73]. However, 16S is not useful in resolving taxonomic differences beyond genus level and it has limited utility in assessing functional profiles of the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing strain level information, metagenomic approaches also have the potential to reveal functional differences (e.g., those obtained via KEGG module analysis) that provide a deeper understanding of the functions of the gut microbiome. A handful of studies have already implemented a shotgun metagenomics approach to delineate the role of microbiome in animal health and diseases [8,12,63,69,73]. If deep shotgun sequencing is prohibitively expensive, shallow-depth shotgun sequencing may be alternative to 16S sequencing as it can provide species and/or strain level taxonomic resolution as well as functional data at approximately the same cost as 16S sequencing [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous canine cancers represent one of the best animal models of human cancers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Being naturally occurring, heterogeneous and with an intact immune system, they capture the essence of human cancer, unlike most genetically modified or xenograft rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…We applied our KPR assembler ( Figure 1) to our canine RNA-seq data, 27 to 87 million pairedend reads of 76x76bp or 50x50bp each of dogs with various cancers 19,[26][27][28] . We then performed Sanger sequencing on 13 samples to validate the assembled contigs.…”
Section: Contigs Assembled By Our Tools Are Validated By Sanger Sequementioning
confidence: 99%